Mean Platelet Volume Enhances the Diagnostic Specificity of PSA for Prostate Cancer - Song, Wei; Ding, Ning; Zhang, Xiulin; Liu, Jiaxin; Wang, Yuzhen; Yan, Jieke; Liu, Shuangde (Frontiers in Surgery, 2022)
Mean platelet volume (MPV), an indicator of platelet activation, has been proposed as a diagnostic marker for several kinds of cancers. We investigate the value of MPV as a diagnosis marker for prostate cancer and examine whether MPV in combination with PSA could increase the sensitivity or specificity of PSA for PCa diagnosis. 107 pathologically confirmed PCa and 177 non-PCa patients underwent prostate biopsy were retrospectively studied. Clinical data and pre-biopsy hematological parameters were collected. The above parameters were compared between PCa and non-PCa patients. Correlation between MPV and clinical characteristics was analyzed. Receiver operating characteristic (ROC) analysis was used to explore the diagnostic value of MPV for PCa. Among all parameters analyzed, the difference was only found in MPV, PDW and PSA between PCa and non-PCa patients. MPV was significantly decreased and PDW increased in PCa than that of non-PCa men. ROC analysis identified MPV≤9.05fl as a cut-off value for potential PCa with AUC=0.783, 95% CI=0.733-0.833, sensitivity=0.746, and specificity=0.708. AUC and the sensitivity of MPV are comparable with TPSA or FPSA. However, the specificity of MPV is larger than that of TPSA (0.461) or FPSA (0.561). Furthermore, MPV combined with TPSA or FPSA further enhanced the specificity of TPSA (0.844) or FPSA (0.927), but PDW not. These findings suggest MPV could have a predictive value for the diagnosis of PCa. MPV in combination with TPSA or FPSA could enhance the specificity of PSA and thus may reduce the rate of unnecessary biopsy for patients with high level of PSA.